Are there subtypes of bipolar depression?. (20th June 2016) - Perich, T.; Hadzi‐Pavlovic, D.; Frankland, A.; Breakspear, M.; Loo, C.; Roberts, G.; Holmes‐Preston, E.; Mitchell, P. B.
Abstract : Objective: To investigate for subtypes of bipolar depression using latent class analysis (LCA). Method: Participants were recruited through a bipolar disorder (BD) clinic. LCA was undertaken using: (i) symptoms reported on the SCID‐IV for the most severe lifetime depressive episode; (ii) lifetime illness features such as age at first depressive and hypo/manic episodes; and (iii) family history of BD and unipolar depression. To explore the validity of any demonstrated 'classes', clinical, demographic and treatment correlates were investigated. Results: A total of 243 BD subjects (170 with BD‐I and 73 with BD‐II) were included. For the combined sample, we found two robust LCA solutions, with two and three classes respectively. There were no consistent solutions when the BD‐I and BD‐II samples were considered separately. Subjects in class 2 of the three‐class solution (characterised by anxiety, insomnia, reduced appetite/weight loss, irritability, psychomotor retardation, suicidal ideation, guilt, worthlessness and evening worsening) were significantly more likely to be in receipt of government financial support, suggesting a particularly malign pattern of symptoms. Conclusion: Our study suggests the existence of two or three distinct classes of bipolar depression and a strong association with functional outcome.